An autopsy case report of extensive intramyocardial hemorrhage complicated with acute myocardial infarction. Issue 3 (September 2020) - Oka, Satoshi; Nakamura, Jun; Kai, Takahiko; Hoshino, Katsuomi; Watanabe, Kazunori; Abe, Makoto; Yasuda, Kazuyo; Watanabe, Akinori
Abstract: Hemorrhagic myocardial infarction (HMI) is a complication associated with percutaneous coronary intervention (PCI) for acute myocardial infarction (AMI). We carried out a successful PCI for a 59-year old Japanese man presenting with chest pain due to AMI over 5 h. The onset to balloon time was 363 min. The next morning, he suffered cardiogenic shock, even with an auxiliary circulating device, which eventually resulted in death. An autopsy revealed extensive HMI. The necrotic myocardium showed not only coagulation necrosis but also contraction band necrosis which suggests myocardial injury due to late reperfusion. Although the intramyocardial hemorrhage was confined to the necrotic area, it was beyond the perfusion area of the culprit artery. Here, we describe a case of death with severe HMI. HMI can be a serious complication and worsen prognosis. <Learning objective: The aim of primary percutaneous coronary intervention (PCI) for acute myocardial infarction (AMI) is to recanalize the infarct related artery and salvage the ischemic myocardium. However, late reperfusion sometimes leads to hemorrhagic myocardial infarction (HMI) as a result of myocardial injury. To avoid extensive HMI in AMI patients, primary PCI should be performed as soon as possible.>